First record of fruit piercing moths (Lepidoptera: Erebidae) in Colombia. (2018)
During the harvest season in June and July of 2016, there was an unusual drop of tangerine and orange fruits that caused heavy losses in several fruit producing municipalities in the department of Santander, in northeastern Colombia. In some of these fruits, punctures were found, from which soft rotting originated; this damage was unknown to farmers in the region. Nocturnal sampling allowed the detection of two species of fruit piercing moths, Eudocima apta and E. procus, puncturing the fruits. Moth damage changed from being high to disappearing within about two weeks. This is the first report of fruit piercing moths in orange and tangerine crops from Colombia. Simultaneously, 60 km east of the citrus crops, moths were also detected in the Berlin paramo in the municipality of Silos between 3,000 and 3,100 masl, far from any fruit orchard and from the host plants registered for E. apta, suggesting that this was a migratory move.